02.12 Il-38 overexpression induces anti-inflammatory effects in mice arthritis models and in human macrophages in vitro. (1st March 2017) - Boutet, Marie-Astrid; Najm, Aurélie; Bart, Géraldine; Touchais, Sophie; Trichet, Valérie; Layrolle, Pierre; Gabay, Cem; Palmer, Gaby; Blanchard, Frédéric; Goff, Benoit Le
Abstract : Background: IL-38 is a newly characterised cytokine that belongs to the IL-1 family and is expressed in the rheumatoid arthritis (RA) synovial tissue but its exact function and mechanism of action are still misunderstood. Here, we analysed for the first time the effect of IL-38 overexpression in the joints of mice with arthritis and in human macrophages and synovial fibroblasts in vitro . Materials and methods: Articular injections of an adeno-associated virus (AAV2/8) encoding IL-38 were performed in Collagen-Induced Arthritis (CIA), K/BxN Serum Transfer-Induced Arthritis (STIA) and Antigen-Induced Arthritis (AIA) in mice. The effect of IL-38 overexpression was evaluated through clinical scores, histology, immunohistochemistry, microCT and RT-qPCR analysis. In vitro, THP-1 monocytes/macrophages were transduced with a lentiviral vector to overexpress IL-38. Effect of conditioned media from these transduced THP-1 cells was also tested on primary culture: M1 macrophages and fibroblast-like synoviocytes from RA patients (RA-FLS). Results: Clinical inflammatory scores were significantly decreased after AAV IL-38 injection in joints of mice with CIA and STIA, but not AIA. This decrease was accompanied by reduced macrophage infiltration and a decreased expression of Th17 signature cytokines (IL-17, IL-23, IL-22, CCL20, CXCL1). However, IL-38 overexpression had no effect on cartilage or bone destruction. In vitro, THP-1 macrophages expressed significantly less IL-6 and IL-23 after IL-38 overexpression. Conditioned media from these cells, containing released IL-38, was also able to exert an anti-inflammatory effect on human primary M1 macrophages and RA-FLS by reducing their IL-6 expression. Conclusion: This study shows for the first time that IL-38 overexpression attenuates the severity of experimental arthritis in two mice arthritis models. IL-38 may exert its anti-inflammatory effects by decreasing the production of pro-inflammatory cytokines by macrophages and synovial fibroblasts. This effect can lead to the development of novel treatment strategies in arthritis.